2012
DOI: 10.1258/ijsa.2012.011373
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and sexual behaviour among youth clients of hotel-based female sex workers in Dhaka, Bangladesh

Abstract: A cross-sectional study was conducted among youth clients of hotel-based female sex workers (YCHBFSWs) in nine randomly selected hotels in Bangladesh to examine sexual-risk behaviour, condom use and determinants of condom use in last sex, knowledge of HIV, sexually transmitted infection (STI) prevalence and STI care-seeking behaviour. A prestructured questionnaire was used to collect sociodemographic, behavioural, clinical information; urine specimens (before sex) and blood were collected for diagnosis of Neis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…13 Similar subjective risk reduction strategies were found in 2 studies with young clients (aged 15-24 years) of FSW in 9 hotels in Dhaka, Bangladesh, including perception of trust (inconsistent condom use with frequently visited FSW), general cleanliness (clean perceived as uninfected), perceived social status (dark skin equated with lower class and therefore fewer clients), and anal sex (perceived low risk of infection). 14,15 Finally, alcohol and drug use, especially among younger risk populations, were determinants of individual behavior negatively associated with condom use. 16 As with FSW and MSM, people who inject drugs also were found to have a low perceived sense of risk.…”
Section: Condom Usementioning
confidence: 99%
“…13 Similar subjective risk reduction strategies were found in 2 studies with young clients (aged 15-24 years) of FSW in 9 hotels in Dhaka, Bangladesh, including perception of trust (inconsistent condom use with frequently visited FSW), general cleanliness (clean perceived as uninfected), perceived social status (dark skin equated with lower class and therefore fewer clients), and anal sex (perceived low risk of infection). 14,15 Finally, alcohol and drug use, especially among younger risk populations, were determinants of individual behavior negatively associated with condom use. 16 As with FSW and MSM, people who inject drugs also were found to have a low perceived sense of risk.…”
Section: Condom Usementioning
confidence: 99%
“…The total number of these areas is unknown, but they are widespread. In addition, in several areas of cities there are low-rent "hotels", where the "customer" will pay a somewhat higher fee than in the brothel (Haseen et al, 2012). There are also an unknown number of women who are "street prostitutes" (Rahman et al, 2000).…”
mentioning
confidence: 99%
“…The study determines contraceptive status and among which 10 (10.6%) used no method of contraceptive, 49 (52.1%) used condoms only, 30 (31.9%) used both oral contraceptive pills and condoms and 5 (5.4%) used pills only respectively. Hossan reported that 66.2% of the participants stated they used other contraceptive means than condoms and 33.7% participates stated they used condoms sometimes [5]. Mayans et al showed that out of 301 female prostitutes, only 40% uses condoms during sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Female Sex Workers (FSWs) are a high-risk population for STIs and human immunodeficiency virus and also considered to be an important reservoir of STIs. In most parts of Asia and Africa, 80 to 90% of the venereal infections, including gonorrhea and chlamydia, originate from FSWs, a substantial proportion of who have asymptomatic infections [5].…”
Section: Introductionmentioning
confidence: 99%